Respuesta :
Answer:
x^6[tex]\sqrt{x}[/tex]
Step-by-step explanation:
we have:
[tex]\sqrt{x^{13}}[/tex]
we can write:
[tex]\sqrt{x^{13}}[/tex] :[tex]\sqrt{x^{2}*x^{2}*x^{2}*x^{2}*x^{2}*x^{2}*x}[/tex]
we know:
[tex]\sqrt{x^{2}} = x[/tex]
so we have:
[tex]\sqrt{x^{13}}[/tex] =[tex]\sqrt{x^{2}*x^{2}*x^{2}*x^{2}*x^{2}*x^{2}*x}[/tex]
we have:
[tex]\sqrt{x^{2}*x^{2}*x^{2}*x^{2}*x^{2}*x^{2}*x}[/tex]=
[tex]x^{6} \sqrt{x}[/tex]
Answer:
[tex]\large\boxed{\sqrt{x^{13}}=x^6\sqrt{x}}[/tex]
Step-by-step explanation:
[tex]\sqrt{x^{13}}=\sqrt{x^{12+1}}\qquad\text{use}\ a^na^m=a^{n+m}\\\\=\sqrt{x^{12}x^1}\qquad\text{use}\ \sqrt{ab}=\sqrt{a}\cdot\sqrt{b}\\\\=\sqrt{x^{12}}\cdot\sqrt{x}=\sqrt{x^{6\cdot2}}\cdot\sqrt{x}\qquad\text{use}\ (a^n)^m=a^{nm}\\\\=\sqrt{(x^6)^2}\cdot\sqrt{x}\qquad\text{use}\ \sqrt{x^2}=|x|\\\\=|x^6|\sqrt{x}=x^6\sqrt{x}\ \text{because}\ x^6\geq0[/tex]